Toxic effects of fumonisin B1 in mice and its detoxification by cabbage seed extract - Abdual-shahid, Dalia K. (Iraqi Journal of Cancer and Medical Genetics, 2013)
The main objective of this research study the toxic effects by fumonisin B1 (FB1) in mice by studying on haematological parameters (Hb, PCV, RBC, WBC and DWBC), mitotic index and histopathological changes of liver and kidney. The following results which obtained from the current research: The effects of FB1 alone on blood picture were caused significant decrease in Hb, PCV and RBCs count. Total WBCs, neutrophil and eosinophil counts were found to be increased significantly; lymphocytes and basophils were decreased significantly and monocytes were not affected significantly, whereas, no significant differences were noticed in mice treated with cabbage seed extract alone or plus FB1. The results of toxic effects on cytogenic study showed a significant decrease in mitotic index for mice treated FB1 alone, but there were no significant in mice treated with FB1 in combination with cabbage seed extract and no significant difference between mice treated cabbage seed extract alone in comparison with control group. While the histopathological changes, In liver: Showed congestion of central vein with vacuolation of hepatocyte, apoptotic cells and accumulation of inflammatory cells in necrotic areas, also the formation of mitotic figure and single necrotic hepatocyte in group which treated with FB1alone, whereas mice treated with FB1in combination with cabbage seed extract showing regeneration most hepatocytes normal structure. The histopathological study of kidney: Showed atrophy of glomerular tuft, degeneration and necrosis of epithelial lining of proximal and distal convoluted tubules with congestion of blood vessels and wide areas of necrosis in parenchyma, in addition the presences of hyaline casts in urinary tubules due to urinary failure in mice treated with FB1alone, while in mice treated FB1plus cabbage seed extract showed just congestion and cuffing in mice treated with FB1 in combination with cabbage seed extract which indicate that the cabbage seed extract has a protective effects